The Role of Digital Marketing Adaptation in Measuring the Success of MSE in Pinrang Regency - Asis, Andini Putri Ramadhani; Cipto Wardoyo; Farida Rahmawati (Universitas Muhammadiyah Pontianak, 2026)
This study analyzes the influence of the entrepreneurial environment on the success of MSE through digital marketing adaptation as a mediating variable. This study used a quantitative approach with a purposive sampling technique involving 399 respondents. Data were analyzed using SEM-PLS. The results show that the entrepreneurial environment has a significant influence on digital marketing adaptation and MSE success. Furthermore, digital marketing adaptation is proven to mediate the relationship between the entrepreneurial environment and MSE success. These findings provide implications for MSE to optimize the use of digital marketing platforms to increase business success. Keywords: Entrepreneurial Environment; Digital Marketing Adaptation; MSE Success